Peran Teknologi Informasi Dan Komunikasi Dalam Meningkatkan Efisiensi Sistem Pendukung Organisasi - Trisnawati Lubis; Muhammad Irwan Padli Nasution (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
The role of Information and Communication Technology (ICT) in increasing the efficiency of organizational support systems is becoming increasingly important. In the ever-changing business world, ICT has a key role in optimizing organizational operations and its ability to adapt to change. This research analyzes various aspects of the role of ICT in the context of the efficiency of organizational support systems. By referring to the latest literature and through relevant case studies, this research identifies that ICT enables business process automation, increased access to information, improved internal communication, and support in more timely decision making. Through the implementation of software, database management systems, collaboration tools, and data security strategies, ICT helps organizations reduce manual work, increase productivity, and reduce operational costs. In a digitally connected global context, ICT also enables organizations to be more responsive to changes in the market and regulatory requirements. This research states that ICT is a valuable asset in improving the efficiency of organizational support systems. With a commitment to intelligently integrating ICT, organizations can become more competitive and flexible in facing continuous changes in the business world.